A systemic hazard analysis and management process for the concept design phase of an autonomous vessel - Valdez Banda, Osiris A.; Kannos, Sirpa; Goerlandt, Floris; van Gelder, Pieter H.A.J.M.; Bergström, Martin; Kujala, Pentti (Reliability engineering & system safety, 2019)
•A process to analyse and manage hazards in autonomous vessels is proposed.•Safety management begins at the earliest design phase of the autonomous vessel.•The process provides safety controls for autonomous ferries.•The process produces the foundations for a systematic safety management strategy. Autonomous vessels have become a topic of high interest for the maritime transport industry. Recent progress in the development of technologies enabling autonomous systems has fostered the idea that autonomous vessels will soon be a reality. However, before the first autonomous vessel can be released into her actual context of operation, it is necessary to ensure that it is safe. This is a major challenge as the experience of autonomous ships is very limited. This study highlights the need for elaborating a systemic and systematic hazard analysis since the earliest design phase of an autonomous vessel. In particular, it proposes a process for elaborating an initial hazard analysis and management that provides coherent, transparent and traceable safety input information for the design of an autonomous vessel. The process is applied to analyse the hazards of two autonomous vessel concepts for urban transport in the city of Turku, Finland.